Analysis of clinical parameters of white spots on young permanent teeth after their treatment with different dental varnishes - Ranka Knežević; Jovan Vojinović (Биомедицинска истраживања, 2022)
Introduction: . Detection of early carious lesion and its remineraliza tion is the most effective way for caries treatment. The aim of this study is to compare effectiveness of remineralization of the early car ious lesions with different fluoride varnishes. Method: . The research included 30 children, girls and boys, aged 12 and 13, in whom the presence of white lesions on at least two vestib ular surfaces was detected on 60 permanent teeth during a clinical examination by visual method. Gingival status was determined based on bleeding or non-bleeding after probing, activity of the white le sion was visually examined and the size of the lesion was measured. After the measurement, the application of varnishes was performed by the procedure that two different dental varnishes were applied to two different teeth with white lesion in the same person: group I - fluoride varnish with 1.5% non-organic ammonium fluoride, group II - fluoride varnish enriched with minerals with 5% sodium fluoride. Activity, lesion dimensions and gingival status were examined after four, eight and twelve weeks when new varnishes were also applied. Results: . Inactivation of white lesions was recorded in the eighth week, but statistically significant difference was recorded after twelve weeks with 56.2% inactive lesions in the group I and 57.5% in the group II. There was no recorded difference in the lesion activity of the varnishes. Changes in the gingivo-incisal diameter during the vis its amounted to: 3.47 mm/3.59 mm/3.53 mm/3.46 mm for the group I and 3.21 mm/3.19 mm/3.18 mm/3.20 mm for the group II. Changes in mesio-distal diameter amounted to: group I: 2.94 mm/2.81 mm/2.84 mm/2.4 mm; group II: 2.94 mm/2.87 mm/2.89 mm/2.90 mm. Statisti cally significant difference in both diameters was recorded between the first and second visit in the group I (p = 0.0046). There was no sta tistically significant difference recorded in the group I during other visits. In the group II statistically significant differences in the chang es of lesion dimension were not recorded. Statistically significant dif ferences p< 0.001 were recorded in the presence of gingival bleeding between the examined groups at the first visit, where significantly more lesions with healthy gingiva were observed in group I (84.4%). Conclusion: . Dental fluoride varnishes cause remineralization of early carious lesion after twelve weeks without significant difference be tween classic and enriched varnishes.
Keywords: caries; white lesion; fluoride; remineralization